Formation of university teaching staff’s readiness towards smart technologies usage - Smagulova, G.Zh.; Kassymov, S.S. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
Effective overcoming of difficulties with updating hardware and increasing the readiness of teachers to use smart-technologies in educational activities, related to the rapid development of computer technologies, possibility of introducing an auxiliary author's software product, which would provide planning, systematization, and structuring of teachers' activities on the use of smart-technologies in the educational process in the conditions of blended learning. The main purpose of this study is to develop and test the effectiveness of the software product “SMART Assistant”, which would contribute to the formation of readiness of teaching staff to effectively use smart technologies in educational activities. The author's software product “SMART Assistant”, which organizes the personal educational environment of a teacher in accordance with the identified stages of professional activity of a teacher ― design, implementation, analysis, optimizing the interaction of participants of the educational process and systematizing the existing range of Smart-services and tools, was used as a tool to form the readiness of teaching staff to use Smart-technologies. The novelty of this study is to identify the impact of the author's software product “SMART Assistant”, introduced in the educational process at the Faculty of Foreign Language of E.A. Buketov Karaganda University, on the level of readiness of teaching staff to the effective use of smart technologies. The results of experimental work on the implementation of the software product “SMART Assistant” confirmed the hypothesis of the study, indicating that its application in the educational process leads to an increase in the level of teachers' readiness for educational activities with the use of smart technologies in the aspect of the identified components of readiness: motivational, cognitive, activity.
Жоғары оқу орындарында профессорлық-оқытушылық құрамының смарт-технологияларды пайдалануға дайындығын қалыптастыру
Формирование готовности педагогических кадров вуза к использованию смарт-технологий
Keywords: smart technologies; digital technologies; smart education; online services; blended learning; teacher readiness; software product “SMART Assistant”; personal digital educational environment of a teacher